The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00127-007-0201-4
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of self-reported emotional and behavioral problems in Greek adolescents

Abstract: Our results confirm that social factors, including negative family functions, lack of academic motivation and not having close friends, were associated with emotional and behavioral problems among adolescents and imply the need to develop a supportive social network for adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
15

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 34 publications
3
19
0
15
Order By: Relevance
“…Tras la lectura de los resúmenes seleccionados, se excluyeron 223 artículos más por no cumplir alguno de los criterios de inclusión. La muestra final de los estudios publicados en revistas contuvo 21 artículos sobre 17 estudios diferentes [6][7][8][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Tras la lectura de los resúmenes seleccionados, se excluyeron 223 artículos más por no cumplir alguno de los criterios de inclusión. La muestra final de los estudios publicados en revistas contuvo 21 artículos sobre 17 estudios diferentes [6][7][8][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] .…”
Section: Resultsunclassified
“…También debemos ser prudentes a la hora de generalizar estos resultados a toda la población de jóvenes debido a que algunos estudios se llevaron a cabo en muestras de conveniencia, que pueden ser poco representativas de la población general y no permiten generalizar sus conclusiones a la población de referencia 15,20,23,24,40 . Sin embargo, el objetivo de esta revisión no es dar recomendaciones precisas sobre Salud Sexual sino describir, de un modo general, los conocimientos, actitudes y prácticas sexuales de los jóvenes europeos.…”
Section: Discussionunclassified
“…The methods of selection and follow-up of the cohort have been previouslydescribed [11][12][13]andaresummarizedbriefly.…”
Section: Methodsmentioning
confidence: 99%
“…For each survey, the questionnaireswerekeptanonymous.Furthermore,duetothefactthat theGreekadolescentparticipantsrespondedtothequestionnaireshortly before their university entry examinations, the attrition was relatively high. Nevertheless, sensitivity analyses showed that the follow-up data was well representative of the initial Greek birth cohort from whom it was selected [12,13]. The participants contacted in 2001 did not differ significantly from participants lost to follow-up in background factors suchaslivingarea,mother'smaritalstatusorbirthweight,butgirlswere slightly overrepresented, and parents' social class was slightly higher in the follow-up group than in the sample lost to follow-up.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…10-18 CDI total score). Few published studies have investigated emotional and behavioural problems among Greek school-aged children and adolescents with regard to their school performance or in comparison to data from different cultural settings [4,23]. The results of these studies present increased rates of children with emotional or/and behavioural problems compared to results of international studies.…”
Section: Introductionmentioning
confidence: 99%